Surviving Sepsis Campaign: association between performance metrics and outcomes in a 7.5-year study - Levy, Mitchell M.; Rhodes, Andrew; Phillips, Gary S.; Townsend, Sean R.; Schorr, Christa A.; Beale, Richard; Osborn, Tiffany; Lemeshow, Stanley; Chiche, Jean-Daniel; Artigas, Antonio; Dellinger, R. Phillip (Intensive care medicine, 2014)
Purpose To determine the association between compliance with the Surviving Sepsis Campaign (SSC) performance bundles and mortality. Design Compliance with the SSC performance bundles, which are based on the 2004 SSC guidelines, was measured in 29,470 subjects entered into the SSC database from January 1, 2005 through June 30, 2012. Compliance was defined as evidence that all bundle elements were achieved. Setting Two hundred eighteen community, academic, and tertiary care hospitals in the United States, South America, and Europe. Patients Patients from the emergency department, medical and surgical wards, and ICU who met diagnosis criteria for severe sepsis and septic shock. Methods A multifaceted, collaborative change intervention aimed at facilitating adoption of the SSC resuscitation and management bundles was introduced. Compliance with the SSC bundles and associated mortality rate was the primary outcome variable. Results Overall lower mortality was observed in high (29.0 %) versus low (38.6 %) resuscitation bundle compliance sites ( p < 0.001) and between high (33.4 %) and low (32.3 %) management bundle compliance sites ( p = 0.039). Hospital mortality rates dropped 0.7 % per site for every 3 months (quarter) of participation ( p < 0.001). Hospital and intensive care unit length of stay decreased 4 % (95 % CI 1–7 %; p = 0.012) for every 10 % increase in site compliance with the resuscitation bundle. Conclusions This analysis demonstrates that increased compliance with sepsis performance bundles was associated with a 25 % relative risk reduction in mortality rate. Every 10 % increase in compliance and additional quarter of participation in the SSC initiative was associated with a significant decrease in the odds ratio for hospital mortality. These results demonstrate that performance metrics can drive change in clinical behavior, improve quality of care, and may decrease mortality in patients with severe sepsis and septic shock.